Petroleum, industry, and governments : an introduction to petroleum regulation, economics, and government policies - Taverne, Bernard, 1932- (The Hague ; Boston : Kluwer Law International, 1999)
This work provides an overview of the regulatory, economic and policy forces which have shaped the organization, development and internationalization of the petroleum industry, focusing on the role of industry and government in the production and use of petroleum. The author analyzes the development and working of the oil and natural gas markets, including issues such as the cost of supply and the establishment of producer prices, and the government policies underpinning the scope, objectives and structure of petroleum legislation.
Includes bibliographical references (p. 403-414) and index.
oif 03/03/15
Loan
Keywords: Oil and gas leases; Petroleum -- Taxation -- Law and legislation; Offshore oil industry -- Law and legislation; Petroleum law and legislation